Health Literacy and Older Adults: Fall Prevention and Health Literacy in a Midwestern State - Amy K. Chesser; Nikki Keene Woods; Jared Reyes; Nicole L. Rogers (Journal of Aging Research And Healthcare, 2018)
Falls continue to be a health concern for older adults. Gender and age are key predictors of falls, particularly for those with low health literacy. Data were collected by a State Health Department using the state-led supplemental question option for the Centers for Disease Control and Prevention (CDC) Behavior Risk Factor Surveillance System (BRFSS) survey. Specifically, trend data for respondents were examined by gender, geographic location and health literacy rate. Results indicated the highest mean number falls occurred with men for those within the metropolitan statistical area (MSA) city code, lowest in suburban areas. Females reported to have a higher estimated mean number of falls and injuries than males. For males, the number of falls and injuries tended to decrease with higher health literacy. The findings support the importance of addressing fall prevention for older adults. Long term implications for improving fall prevention and health literacy for older adults include impact on individual outcomes.
Keywords: health literacy